Specific Mechanical Energy and Thermal Degradation of Poly(lactic acid) and Poly(caprolactone)/Date Pits Composites - A. A. Mohamed; S. Hussain; M. S. Alamri; M. A. Ibraheem; Akram A. Abdo Qasem (International Journal of Polymer Science)
The compatibility of date pits (DP) with polylactic acid (PLA) or polycaprolactone (PCL) is investigated. Composites were prepared by compounding PLA or PCL with date pits at 10, 20, 30, and 40% wt/wt and extruded. Wheat vital gluten (VG) was also used as a filler and in combination with DP. The specific mechanical energy (SME) was calculated and the composites thermal properties were tested using DSC (peak temperature, enthalpic relaxation, and glass transition) and TGA (degradation temperature and mechanism and degradation kinetics). Because DP is hard filler, the SME of PCL-DP composites increased as the amount of filler increased. At 40% fill, the SME decreased due to the lubricating effect of oil found naturally in DP. As illustrated by lower SME, PLA composites exhibited softer texture because PLA is harder than DP. The DSC melting peak temperature of both polymers has increased at higher DP; however, PLA exhibited enthalpic relation between 66 and 68°C. The TGA profile of the composites displayed two distinct peaks versus one peak for the pure polymer. The degradation kinetics showed multistep process for the composites and one-step process for the pure polymer. The utilization of date pits as a hard filler in developing biodegradable plastics is good for the environment and a value added for the date industry.